Concept of corruption (Journal of actual problems of jurisprudence, 2018)
From the point of view of the theory and law-enforcement practice of investigation and prevention of corruption crimes, conducting legal proceedings on them are integral part of the criminal and criminal procedure law. Unfortunately, as the reason for that serves growth in the country corruption a crime from year to year. In this article authors consider concept of corruption, thought and definition of some scientists, the offenses creating conditions for corruption and responsibility for them, the importance of the specified problems today.Key words: the criminal trial, corruption, bribery, a bribe, the official, offenses creating conditions for corruption, punishment.